2005
DOI: 10.4102/ojvr.v72i1.219
|View full text |Cite
|
Sign up to set email alerts
|

Some preliminary observations on the susceptibility and resistance of different cattle breeds to <i>Theileria parva</i> infection

Abstract: Theileria parva-naïve Friesian (Bos taurus), Boran (Bos indicus) and Maasai Zebu steers (B. indicus) were infected with a T. parva sporozoite stabilate dose which had previously been shown to induce an estimated 50 % mortality rate in Boran cattle. All the cattle developed patent infections with no significant differences in the length of the prepatent period to development of macroschizonts (P > 0.05) between the three groups. Clinical theileriosis occurred in all eight the Friesians (100 %), five out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…in crossbred cattle than in Sahiwal. On the other hand, Ndungu et al [ 45 ] reported that different cattle breeds enrolled in their study were equally susceptible to Theileria infection, but there was a marked difference in their development of clinical theileriosis. differences in the parasite prevalence among cattle breeds from various studies is probably due to the different total number of samples, and due to different breed enrolment of cattle these studies.…”
Section: Discussionmentioning
confidence: 95%
“…in crossbred cattle than in Sahiwal. On the other hand, Ndungu et al [ 45 ] reported that different cattle breeds enrolled in their study were equally susceptible to Theileria infection, but there was a marked difference in their development of clinical theileriosis. differences in the parasite prevalence among cattle breeds from various studies is probably due to the different total number of samples, and due to different breed enrolment of cattle these studies.…”
Section: Discussionmentioning
confidence: 95%
“…As there was only one breed of cattle sampled during this study, no relationship between TBDs seroprevalence and breed could be assessed. However, recent work by Ndungu et al. (2005) on the susceptibility of different cattle breeds to T. parva infection indicated that zebu cattle were highly successful in developing a higher degree of resistance than either Boran or Friesian cattle.…”
Section: Discussionmentioning
confidence: 99%
“…However, for many years, indigenous (Bos indicus) cattle have been known to be less susceptible to T. parva infections than exotic (Bos taurus) cattle (Ndungu et al 2005). …”
Section: Discussionmentioning
confidence: 99%